FIRST STRUCTURE DETERMINATION OF AN MDO-2O MICA POLYTYPE ASSOCIATED WITH A 1M POLYTYPE - Ferraris G.; Gula A.; Ivaldi G.; Nespolo M.; Sokolova E.; Uvarova Y.; Khomyakov A.P. (My University, 2001)
The structure refinement of associated phlogopite-2O and phlogopite-IM from the Khibiny massif (Kola Peninsula, Russia) is reported. Crystal data are: a = 5.2781(5), b = 9.141(1), c = 20.124(4) Angstrom, Ccmm (2O); a = 5.305(2), b = 9.199(2), c = 10.232(4) Angstrom, beta = 100.03(2)degrees, C2/m (1M). Least-squares refinement of single-crystal X-ray diffraction data converged to R1 = 0.034 (2O, 926 independent reflections) and 0.037 (1M, 677 independent reflections). This is the first structure refinement of an MDO (standard) mica-2O: two previous structure reports concern anandite-2O, which was not a true polytype, having an oP (primitive orthorhombic) lattice not compatible with the C-centred cell common to all mica polytypes. The two phlogopite polytypes show practically the same chemical composition (K0.95Na0.01)(Mg2.16Fe0.34Ti0.04Mn0.04Li0.40)[Si3.40Al0.60O10][(OH)(1.35)F-0.65 ] and no cation ordering. Both polytypes are affected by stacking disorder, which broadens the non-family reflections (k not equal 3n). As a consequence, the diffracted intensities of the two types are measured at different scales and large residues in the difference Fourier maps were observed at +/- b/3 along [010], [310] and [3 (1) over bar0]. These residues (Durovic effect) disappear by carrying out the refinement with separate scale factors for the two types of reflections. On the basis of structural, morphology and zoning considerations the formation of the two associated polytypes is attributed to chemical oscillation in the crystallization mean.
Keywords: phlogopite-2O; phlogopite-1M; crystal structure; polytypism; stacking disorder